Digital Connectivity in Lao PDR – Lagging Behind Peers : A Short Assessment with Policy Recommendations to Catch Up - World Bank Group (World Bank, Vientiane, 2019)
Digital connectivity—access to affordable and reliable internet services—has become a key driver of economic and social development globally. Economic activities and government services are increasingly moving online. Lao PDR is well-positioned to take advantage of these trends to improve growth, competitiveness and services provision to the population, but urgent interventions are needed to ensure that Lao PDR does not fall further behind regional peers. This note reviews the status of digital connectivity in Lao PDR and options for improvement, including the respective roles of government and industry. The main findings are as follows: By almost every measure, Lao PDR is lagging significantly in terms of accessibility, quality and affordability of internet services compared to other comparable regional economies. Access to mobile broadband is increasing, but rural and more remote communities are still unserved or underserved. Actions to close this digital divide are needed urgently. Fixed broadband—required for high-capacity data transmission to support the next wave of digital development—is particularly limited. Prices for internet are comparatively high. High capacity fixed broadband services are very limited and extremely expensive. The minimum retail tariff regime for mobile, voice and data services may reduce the ability of operators to differentiate services and compete on price and service quality. Quality of service and affordability of internet are continuing concerns which are slowing the introduction and use of digital services and applications. Regulatory capacity and expertise is increasing, but remains comparatively low which is further limiting market growth and investment.